correction of problem. Should be:
-2x squared + 6x + 5 = 0
Sorry about that!
Thanks for your help!
Use "completing the square" to find the zeros of the polynomial.
=2x squared + 6x + 5 = 0
2 answers
well, this one is different anyway
-2 x^2 + 6 x + 5 = y find zeros
x^2 - 3 y - 2.5 - -y/2
x^2 - 3 y = -y/2 + 5/2
x^2 -3 y + 9/4 = -2 y/4 + 10 y/4 + 9/4
(x- 3/2)^2 = -1/2 (y -19/2)
when y = 0
(x-3/2)^2 = 19/4
so
x = 3/2 +/- 1/2 sqrt 19
check with quad eqn
x = [ -6 +/- sqrt (36 +40) ]/-4
= 3/2 +/- sqrt (76)/4
= 3/2 +/- 2 sqrt 19/4
= 3/2 +/- (1/2) sqrt 19 sure enough
-2 x^2 + 6 x + 5 = y find zeros
x^2 - 3 y - 2.5 - -y/2
x^2 - 3 y = -y/2 + 5/2
x^2 -3 y + 9/4 = -2 y/4 + 10 y/4 + 9/4
(x- 3/2)^2 = -1/2 (y -19/2)
when y = 0
(x-3/2)^2 = 19/4
so
x = 3/2 +/- 1/2 sqrt 19
check with quad eqn
x = [ -6 +/- sqrt (36 +40) ]/-4
= 3/2 +/- sqrt (76)/4
= 3/2 +/- 2 sqrt 19/4
= 3/2 +/- (1/2) sqrt 19 sure enough